Mechanical Synchrony and Myocardial Work in Heart Failure Patients With Left Bundle Branch Area Pacing and Comparison With Biventricular Pacing - Liu, Wen; Hu, Chunqiang; Wang, Yanan; Cheng, Yufei; Zhao, Yingjie; Liu, Yang; Zheng, Shaoxin; Chen, Haiyan; Shu, Xianhong (Frontiers in Cardiovascular Medicine, 2021)
Background: Little is known about the efficacy of permanent left bundle branch area pacing (LBBAP) in delivering cardiac resynchronization therapy. This study aimed to evaluate the effect of LBBAP on mechanical synchronization and myocardial work in heart failure (HF) patients and to compare LBBAP with biventricular pacing (BVP). Methods: This is a multicenter, prospective cohort study. From February 2018 to January 2021, 62 consecutive heart failure patients with reduced ejection fraction (LVEF≤35%) and CLBBB who underwent LBBAP or BVP were enrolled in this study. Echocardiograms and electrocardiograms and were conducted before and 3-6 months after implantation. Intra- and interventricular synchronization were assessed using two-dimensional speckle tracking imaging (2D-STI). The left ventricular pressure-strain loop was obtained by combining left ventricular strain with noninvasive blood pressure to evaluate mechanical efficiency. Results: The echocardiographic response rates were 68.6% and 88.9% in the BVP and LBBAP groups, respectively. LBBAP resulted in significant QRS narrowing (from 177.1±16.7 ms to 113.0±18.4 ms, P < 0.001) and improvement in LVEF (from 29.9±4.8% to 47.1±8.3%, P < 0.001). The global wasted work (GWW) (410.3±166.6 mmHg% vs 283.0±129.6 mmHg%, P =0.001) and global work efficiency (GWE) (64.6±7.8% vs 80.5±5.7%, P < 0.001) were significantly improved along with shorter peak strain dispersion (PSD) (143.4±45.2 ms vs 92.6±35.1 ms, P <0.001) and interventricular mechanical delay (IVMD) (56.4±28.5 ms vs 28.9±19.0 ms, P <0.001), indicating its efficiency in improving mechanical synchronization. In comparison with BVP, LBBAP delivered greater improvement of QRS narrowing (-64.1±18.9 ms vs -32.5±22.3 ms, P < 0.001) and better mechanical synchronization and efficiency. Conclusions: LBBAP was effective in improving cardiac function, mechanical synchronization and mechanical efficiency and may be a promising alternative cardiac resynchronization therapy. Key Words: Cardiac resynchronization therapy; Heart failure; Left bundle branch block; Myocardial work; Mechanical Synchronization